A quantitative insight of the interactions of prescribers with pharmaceutical organization’s representatives in clinical settings of Karachi - Shakeel, Sadia; Nesar, Shagufta; Iffat, Wajiha; Fatima, Bilqees; Maqbool, Tahmina; Jamshed, Shazia Qasim (Dove Press Ltd, 2019)
Objectives: The study was conducted with the aim to evaluate the prescribers’ approach of interaction with medical representatives for drug promotion. Methods: An explanatory, cross-sectional design was used to evaluate prescribers’ interactions with the medical sales representatives (MSRs) through an anonymous, self-filled questionnaire from June to December 2017. Data presented as means±SEM or as percentages and statistically analyzed by one way ANOVA, using significance level of 0.05. Results: A response rate of 82.8% was achieved. More than 70% agreed that knowledge obtained from MSRs is reliable and useful. A large proportion of respondents acknowledged that MSRs are a key link between pharmaceutical companies and health care professionals, and their interactions are beneficial as MSRs perform an important teaching function. More than 45% agreed that gifts are influential; however, physicians cannot be compromised with very expensive gifts. The majority of the respondents (76%) considered that promotional items are ethically appropriate; however, 66.21% thought that promotional items influence the practice of prescribing. More than half (52.18%) deemed a promotional material more reliable than a printed advertisement. More than 80% of the respondents opined that medication samples are considered appropriate; however, they should only be given to those patients who cannot financially afford them. Around 69% thought that companysponsored meetings promote their own drugs under the disguise of CME programs. Conclusion: The present study emphasizes the importance of employing scientifically sound prescribing decision by prescribers in their day to day practice without being influenced by pharmaceutical company’s promotional activities. There is a need for restricting unprincipled practices by the concerned regulatory authorities to evade preventable harm to the patient’s well-being.